Gramsci’s «Prison Notebooks» and the “re-foundation” of anthropology in post-war Italy - Satta, Gino (International Gramsci Journal, 2023)
In the 1970s, when the identity of Italian “demo-ethno-anthropological” studies was being defined and their academic status consolidated, scholars debated the features of a national tradition of studies. Antonio Gramsci’s Prison Notebooks were then presented as the source of new ideas, which in the aftermath of WWII contributed in decisive ways to a renewal of scholarly theory, helping scholars to get rid of romantic leftovers such as the notion of “people-nation”, and encouraging them to turn away from “picturesque” oddities to address important social and cultural issues. This inscription of Gramsci into the genealogy of Italian anthropological studies, which recognizes the important role his thought played in scholarly debates, nonetheless risks concealing the different readings his reflections received when they were first published soon after the war (1948-1951). The paper focuses on the debate regarding Gramsci and folklore organized by the Gramsci Institute in Rome in the late spring of 1951, in order to sketch out an array of very different readings of Gramsci’s contribution to the study of folklore. On that occasion Paolo Toschi, a recognized and distinguished scholar, dismissed Gramsci’s theoretical contribution and presented Gramsci as an amateur folklorist, while Ernesto De Martino, a young scholar still in search of academic recognition, gave a very one-sided and political interpretation of Gramsci’s thought, which he was later to radically rethink. Alberto Cirese, attending the debate as a very young man, was later to propose a third and very influential reading of Gramsci’s observations. Through the prism of these different readings, the post-war Gramscian moment of Italian anthropology appears as something much more complex and controversial than 1970s accounts would have it.